Benzydamine hydrochloride for the treatment of sore throat and irritative/inflammatory conditions of the oropharynx: a cross-national survey among pharmacists and general practitioners - Desiderio Passali; Maria Felice Arezzo; Alessandra De Rose; Gianmarco De Simone; Gianluigi Forte; Michalina Jablko-Musial; Ralph Mösges (BMC Primary Care, 2022)
Abstract Background Benzydamine for oromucosal use is indicated in the relief of pain and irritation of the mouth and throat. It is an indazole derivative, non-steroidal anti-inflammatory drug, with combined local anesthetic and analgesic properties, and antiseptic activity, marketed under the brand name “Tantum Verde”. The aim of this study was to explore knowledge and prescriptive/advising attitudes among general practitioners (GPs) and pharmacists (PHs) with regard to the topical treatment of sore throat and other irritative/inflammatory conditions of the oropharynx, with a focus on benzydamine. These findings could be important to increase awareness on benzydamine efficacy in sore throat and stomatological conditions, and to reinforce knowledge on the characteristics of benzydamine and its mechanisms of action among healthcare professionals (pediatricians, otolaryngologists, oncologists, etc.). Materials and methods An online questionnaire survey was performed among PHs and GPs in four European countries (Italy, Germany, Russia and Poland). Results Both GPs and PHs proved to have an excellent knowledge and mastery of the constituents effective against oral symptoms. Among all the principles, benzydamine hydrochloride is the most recognized as certainly suitable for the topical treatment of sore throat symptoms and various inflammatory/irritative conditions of the oral cavity. It is recommended by about 90% of PHs and prescribed by 80% of GPs, mainly to solve the ailments caused by sore throats and stomatitis, especially for its anti-inflammatory, analgesic and anesthetic characteristics. Also in the pediatric field, benzydamine hydrochloride is recommended: among GPs, a high percentage (about 40%) prescribes it like the remedies based on dichlorobenzyl alcohol-sodium benzoate, which are instead more often recommended by PHs (44% against 37%). Conclusion Although the public has a lot of confidence in this treatment, GPs and PHs do not recommend/prescribe benzydamine as a first-line treatment of sore throat and other irritative/inflammatory conditions of the oropharynx. To increase the knowledge of benzydamine among these healthcare professionals, it would be important to emphasize its characteristics and the different irritative/inflammatory conditions of the oropharynx in which it can be used.